Acetyldiaminobutanoic acid, a potential lathyrogenic amino acid in leaves of Acacia angustissima - Reed, J.D.; Gebre-Mariam, G.; Robinson, C.J.; Hanson, Jean; Odenyo, A.A.; Treichel, P.M. (Wiley, 2001)
Acacia angustissima has potential in agroforestry systems for forage production in tropical environments. However, feeding trials indicate that the leaves are potentially toxic. Signs of toxicity in sheep are similar to those presented by sheep fed flatpea (Lathyrus sylvestris) hay which contains a high concentration of the non-protein amino acid 2,4-diaminobutanoic acid (DABA). Cation exchange chromatography, high-performance liquid chromatography (HPLC) and NMR were used to isolate and identify the non-protein amino acid in A angustissima leaves. A quantitative HPLC method was used to determine the content of the non-protein amino acid in leaves from 20 accessions. The non-protein amino acid was identified as 4-N-acetyl-2,4-diaminobutanoic acid (ADAB), previously reported to occur in seeds. The average and range in ADAB content were 16.8 and 10.6-25.4mgg -1 respectively. This content of ADAB is higher than the levels of DABA in flatpea hay that are toxic to sheep.